Análise mista das imagens em livros didáticos de química de segunda série do ensino médio - Souza, Ivan Pollarini Marques de (2018)
The present work was devoted to the study of the images contained in chemical textbooks approved in PNLD-2015. It aimed to classify the nature of the images contained in the themes Solutions and Colligative Properties according to the categories proposed in the taxonomy of images proposed by authors of the area, in addition to classic themes of PNLD-2015. The theoretical framework was based on the Theory of Semiotics by Charles Pierce and the Triangle of Johnstone and Johnstone-Kiill. The results obtained in this work show the predominance of the use of inoperative photographs in the textbooks, being these linked to the text by means of verbal labels. The images favor the Macroscopic dimension to the detriment of other dimensions, weakening the understanding of chemical concepts at the submicroscopic level, as well as the low percentage of images and texts that deal with the History of Science, contributing to the conception of individualistic, elitist and perfect Science.